Business models of FinTechs – Difference in similarity? - Laidroo, Laivi; Koroleva, Ekaterina; Kliber, Agata; Rupeika-Apoga, Ramona; Grigaliuniene, Zana (Elsevier B.V., 2021)
The FinTech industry is gradually maturing and offers a wide range of financial services on the global stage. Still, the understanding of FinTech business models remains at its infancy with a shortage of cross-country comparisons. This paper aims to determine the differences in business model attributes of FinTechs in five rapidly emerging FinTech hotspots in Central and Eastern Europe (CEE). Survey results from Estonia, Latvia, Lithuania, Poland, and Russia, accompanied by cluster analysis, enable us to provide unique in-depth evidence on FinTech business models. Across the selected countries, we observe significant differences in the attributes of FinTech business models: key activities, key resources, value propositions, customer segments, delivery channels, cost structure, and revenue stream. We identify four clusters of FinTechs: “lending community”, “mixed services”, “payment service”, and “payment community”. Although these clusters share similarities with FinTech archetypes proposed in previous research, they remain rather unevenly distributed across countries.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies; FinTech; Business models; Business model attributes; Business model canvas; FinTech ecosystem